Epigenetic therapy can inhibit growth of ovarian cancer cells and reverse chemoresistant properties acquired from metastatic omentum1. Issue 2 (15th March 2019) - Sookram, Janhvi; Zheng, Andrew; Linden, Kimberly M.; Morgan, Andrew B.; Brown, Spencer A.; Ostrovsky, Olga
Abstract: Objective: To examine the cytotoxicity of epigenetic drugs independently and in combination with chemotherapy on ovarian cancer cells Caov‐3, and to investigate their ability to acquire chemoresistance in omental microenvironments and whether epigenetic drugs can counteract this chemoresistance. Methods: A pilot study was conducted in Cooper University Hospital, NJ, USA from August 1 to October 31, 2017, among women undergoing surgeries for uterine and ovarian cancer. Cytotoxicity assays using IC50 values of epigenetic drugs and paclitaxel and cisplatin were performed on Caov‐3. Omental adipose‐derived stem cells (OASCs) were isolated from omentum with/without metastases. Caov‐3 was cultured with OASCs' conditioned medium and subjected to different drugs. Cell viability and secretome was measured using MTT and Elisa, respectively. Results: Three women met the eligibility criteria and were included in the study. Epigenetic drugs alone or in combination with chemotherapy showed 85%–94% increased cytotoxicity against Caov‐3 ( P ≤0.005). Metastatic OASCs conditioned medium showed up to 27‐fold increase in tumorigenic factors and promoted chemoresistance (28%–35%; P < 0.050) against chemotherapy. Epigenetic therapy resulted in up to a 40‐fold reversal in this chemoresistance. Conclusion: Epigenetic therapies could have an important role in treating a subgroup of ovarian cancer patients that demonstrate resistance to first‐line chemotherapy. Abstract : Epigenetic drugs alone or in combination with classic chemotherapy significantly increase cytotoxicity in ovarian cancer cells and reverse chemoresistance imparted by metastatic omental microenvironment.